(untitled) (REMUNOM, 2025)
COVID-19 is a severe acute respiratory syndrome that requires a clinical picture of asymptomatic infections to severe conditions. Thus, it is believed that this pandemic caused a global increase in disorders such as depression and anxiety. As a result, the search for relief from symptoms of anxiety and depression through medication increased. to analyze the increased use of antidepressants and anxiolytics in the post-COVID-19 pandemic period and its impacts on society. The research was an integrative review. The selection of articles was carried out with emphasis on the Virtual Health Library (VHL) databases, through the Latin American and Caribbean Literature in Health Sciences (Lilacs) database; the Scientific Electronic Library Online (ScIELO), was carried out involving the combined descriptors using Boolean operators: AND and OR, and Health Sciences Descriptors (DECS). After searching the databases, 8 articles were selected to conduct the results and discussions. In the post-pandemic period, there was an increase in the use of psychotropic medications, which can be attributed to the growing awareness and recognition of mental health disorders in society. Prescription rates for antidepressants and anxiolytics increased significantly during the pandemic, reflecting a growing need for mental health support among the population. Conclusion: The work concludes by showing that the use of anxiolytics and antidepressants increased significantly during the pandemic and post-pandemic periods, which had a series of consequences that affected people’s mental health, which led to the search for medicalization.